Implementation of Fuzzy Method towards Hydroponic Smart Showcase Innovation - Sembiring, Sarmayanta; Exaudi, Kemahyanto; Prasetyo, Aditya PP; Rendyansyah, Rendyansyah; Nadhira, Wardha (Emitor: Jurnal Teknik Elektro, 2024)
Hydroponics is a technique that allows easy cultivation of fresh and hygienic vegetables, even with limited space. Recent innovations in hydroponic development have resulted in a smart showcase prototype, which is controlled using Sugeno fuzzy techniques. This prototype uses a DC fan to maintain a stable temperature and humidity level. This invention is both ecologically friendly and portable, making it suitable for a wide range of users, including apartment residents. Experimental results using the fuzzy method show that this prototype can effectively support indoor hydroponic techniques, with fan rotation ranging from 180 to 255 rpm based on variations in room temperature and humidity. The showcase successfully maintained a stable temperature range of 28–30 °C and a humidity of 60–70% RH. In addition, out of 12 vegetable samples tested for 14 days, 7 kale stems showed significant growth. Overall, this smart showcase prototype offers the potential to bring hydroponics indoors and promote fresh vegetable cultivation.